Synthesis and characterization of crosslinked polymers from cottonseed oil. Issue 24 (21st February 2019) - Wijayapala, Rangana; Mishra, Satish; Elmore, Bill; Freeman, Charles; Kundu, Santanu
ABSTRACT: Traditional plastics are usually obtained from nonrenewable petroleum feedstocks. In this study, crosslinked polymers were synthesized from cottonseed oil. Unsaturated fatty acids, the major components of cottonseed oils, were initially epoxidized. A network polymer was then formed by crosslinking the epoxidized oil with maleic anhydrate. Mechanical properties of these polymers were altered by varying the amount of maleic anhydrate. These polymers have a tensile modulus of the order 1 MPa and are stable in the acidic and alkaline environment. Our results provide a new synthetic strategy to obtain a network polymer from cottonseed oil. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47655. Abstract :